2007
DOI: 10.7589/0090-3558-43.4.635
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Eastern Equine Encephalitis Virus in Free-Ranging White-Tailed Deer in Michigan

Abstract: Eastern equine encephalitis (EEE) virus has been recognized as affecting horses and humans in the eastern United States for 70 yr. Evidence of exposure with EEE virus has been reported in a variety of free-ranging wild birds and mammals but cases of clinical disease are much less commonly reported. In Michigan, reports of outbreaks of EEE virus in equine species extend back more than a half century. We report diagnosis of EEE virus infection of multiple free-ranging white-tailed deer (Odocoileus virginianus) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 20 publications
(21 reference statements)
2
38
1
Order By: Relevance
“…The overall seropositivity rate of 10.2% in this study is similar to the 14% rate found in Georgia and the 7.1% rate found in Maine in 2010. [17][18][19] Culiseta melanura, the primary enzootic vector, and Coquillettidia, Culex, and Aedes spp., which are likely bridge vectors of EEEV, have previously been documented in Vermont. 9,16 These potential bridge vectors are widely distributed in Vermont, but the distribution of Cs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall seropositivity rate of 10.2% in this study is similar to the 14% rate found in Georgia and the 7.1% rate found in Maine in 2010. [17][18][19] Culiseta melanura, the primary enzootic vector, and Coquillettidia, Culex, and Aedes spp., which are likely bridge vectors of EEEV, have previously been documented in Vermont. 9,16 These potential bridge vectors are widely distributed in Vermont, but the distribution of Cs.…”
Section: Discussionmentioning
confidence: 99%
“…The white-tailed deer has been shown to be a reasonable sentinel species that is frequently exposed to EEEV. [17][18][19][20] White-tailed deer also represent a large proportion of the mammalian source for blood meals for the most common bridge vector species. 21 In addition, white-tailed deer have a summer home range that is about 1 mile in radius, to which they return faithfully.…”
Section: Introductionmentioning
confidence: 99%
“…This species was selected as a sentinel for several reasons. First, several previous studies in the US (Hoff et al 1973, Bigler et al 1975, Tate et al 2005, Schmitt et al 2007) have reported EEEV antibody-positive sera among populations of free-ranging O. virginianus, demonstrating that deer frequently become infected with EEEV. Second, white-tailed deer form a significant proportion of the blood meals of EEEV bridge vectors, particularly Cq.…”
Section: Introductionmentioning
confidence: 97%
“…The virus has been isolated from birds and other mammals such as equines, sheep, cattle, and deer as well as mosquitoes throughout these regions (Carman, et al, 1995;Gibbs, 1976;McGee, et al, 1992;Schmitt, et al, 2007). Cotton rats and house sparrows have been proposed as other hosts for the virus (Arrigo, et al, 2010).…”
Section: Transmission Cycles and Geographic Rangementioning
confidence: 99%